USING ALPHA-BETA PARTNERSHIP METHOD IN TEACHING SPEAKING TO THE FIRST SEMESTER STUDENTS OF STAI-BS LUBUKLINGGAU - Joni Helandri (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2018)
The researcher found that some students find it difficult to express their ideas, comments, and thoughts in English. Some students don't even dare to advance in front of the class because they have no ideas to talk about. students are given a short topic to talk about in front of the class. Most of them can't do it well, only a few of them can do the exercises or talk. students need media or games as a facility to improve their English language skills. The aim of the study was to see whether the use of the Alpha-Beta Partnership was effective in teaching speaking to the first semester students of Islamic Education Study Program (PAI) at Bumi Silampari Lubuklinggau Islamic High School (STAI). The method used in this study is a pre-experimental method. Population of 62 students. 30 as a sample. analysis using the Matched T-test. Results The findings of the students' pre-test score were 59.33 and the post-test average score was 70.05. meaning that there is a significant difference between students' ability to speak after they have been taught using the Alpha-Beta Partnership Method.